Evaluating education through dropout: the curse and punishment - Barbosa e Silva, Leonardo (2024)
This article explores the set of theoretical and methodological challenges that have yet to be fully addressed by the scientific community studying dropout in higher education, metaphorically referred to here as a curse. The objective was to systematize the contributions of the literature that identify why the long-standing theoretical frameworks and their application in higher education public policies have not achieved the desired outcome, namely the reduction of dropout rates. To this end, a narrative review of the literature was conducted, drawing on nearly a century of key works in the field. The findings highlight difficulties related to defining the concept (lack of consensus and specificity), as well as methodological challenges, such as the absence of longitudinal, systemic, and integrative approaches that combine qualitative and quantitative research. Lastly, the study emphasizes the importance of identifying specific contexts where dropout is a significant issue and incorporating the right to education as a key analytical variable.